Öğretmenlerin Sanal Sınıf Yönetimi Yeterliliği Ölçeği: Geçerlik ve Güvenirlik Çalışması - Can, Ertuğ; Gündüz, Yüksel (Bolu Abant İzzet Baysal Üniversitesi, 2021)
Bu araştırmanın amacı, öğretmenlerin sanal sınıf yönetimi yeterliğini ölçebilecek bir ölçek geliştirmektir. Genel taramamodelinde yürütülen ölçekleme temelli bu araştırma, öğretmenlerin sanal sınıf yönetimi yeterliği ölçeğinin yapı geçerliğinive iç tutarlılığını tespit etmeyi amaçlamaktadır. Araştırmanın evrenini, 2020-2021 eğitim öğretim yılında Kırklareli ilimerkez ve ilçelerinde görev yapan öğretmenler oluşturmaktadır. Araştırmanın örneklemi, açımlayıcı faktör için 329öğretmenden, doğrulayıcı faktör için 322 öğretmenden oluşmaktadır. Taslak ölçek 5’li likert tipinde ve 25 maddedenoluşmuştur. Açımlayıcı faktör analizi sonucunda ölçeğin 3 faktör ve 24 maddeden oluştuğu tespit edilmiştir. Maddeiçerikleri incelendikten sonra birinci alt ölçeğe “öğrencilerle ilişkiler”, ikinci alt ölçeğe “sanal sınıf içi etkinlikler” ve üçüncüalt ölçeğe “sanal sınıf yönetimi” adı verilmiştir. Test sonucunda "t" değerleri istatistiksel açıdan ,001 düzeyinde anlamlıolduğu için tüm maddelerin ayırdedici oldukları anlaşılmıştır. Ölçeğin güvenirliği, Cronbach Alfa (α) Katsayısı, SpearmanBrown Katsayısı ve Guttman Katsayısı ile yapılan güvenirlik analizleri sonucunda belirlenmiştir. Doğrulayıcı faktör analizisonucuna göre, bütün maddeler ilgili faktörler altında anlamlıdır. Bu sonuçlar, Öğretmenlerin Sanal Sınıf Yönetimi YeterliğiÖlçeği’nin geçerli ve güvenilir bir ölçek olduğunu göstermektedir. Ölçek, öğretmenlerin sanal sınıf yönetimi yeterlikdüzeylerini belirlemek için ulusal ve uluslararası düzeyde bütün öğretim kademelerinde kullanılabilir. Öğretmenlerin sanalsınıf yönetimi yeterlikleri, nitel araştırma yöntemleri kullanılarak daha derinlemesine araştırılabilir.

The aim of this research is to develop a scale that can measure teachers' virtual classroom management competence. This scale based research that was conducted with general survey model aims to determine the construct validity and internal consistency of the scale of teachers' virtual classroom management competence. The population of the research consists of teachers working in the central and other districts of Kırklareli province in the 2020-2021 academic year. The sample of the study consists of 329 teachers for the explanatory factor and 322 teachers for the confirmatory factor. The draft scale is 5- point likert type scale and consists of 25 items. According to the result of the explanatory factor analysis, it was determined that the scale consists of 3 factors and 24 items. After the item contents were examined, the first sub-dimension was named as "relationships with students", the second sub-dimension was named as "virtual classroom activities" and the third subdimension was named as "virtual classroom management". As the "t" values were statistically meaningful at the .001 level, it was understood that all items were discriminant. The reliability of the scale was determined as a result of the reliability analysis performed with the Cronbach Alpha (α) Coefficient, Spearman-Brown Coefficient and Guttman Coefficient. According to the result of confirmatory factor analysis, all items are meaningful in terms of the related factors. These results show that the scale of Teachers' Virtual Classroom Management Competence is a valid and reliable scale. The scale can be used to determine the level of teachers’ virtual classroom management competencies at all teaching levels at national and international level. Teachers’ virtual classroom management competencies can be investigated more in depth by using qualitative research methods.
The scale of teachers’ virtual classroom management competence: Validity and reliability study
Keywords: Sanal Sınıf; Sınıf Yönetimi; Sanal Sınıf Yönetimi; Yeterlik Ölçeği; Virtual Classroom; Classroom Management; Virtual Classroom Management; Competence Scale